In vitro fermentation characteristics and methane mitigation responded to flavonoid extract levels from alternanthera sissoo and dietary ratios - Sommai, Sukruthai; Cherdthong, Anusorn; Suntara, Chanon; So, Sarong; Wanapat, Metha; Polyorach, Sineenart (My University, 2021)
Two experiments were conducted under this study: Experiment 1 was to study production yield, chemical composition, and in vitro degradability of Brazilian spinach (Alternanthera sissoo; BS) leaf and leaf + leaf-stalk at various maturity ages of 15, 30, 45, and 60 days after plantation and regrowth and Experiment 2 was to evaluate the effect of flavonoid extract from BS leaf and leaf + leaf-stalk and dietary ratios on ruminal gas production, fermentation characteristics, and in vitro degradability. Experiment 1 showed that maturity ages after planting and regrowth increased, the yield significantly increased. Increasing maturity ages significantly (p < 0.05) increased neutral detergent fiber and acid detergent fiber content and decreased crude protein content, total flavonoid (TF) content, and degradability for both leaf and leaf + leaf-stalk. Maturity ages from 15 to 30 days after plantation and regrowth resulted (p < 0.05) the highest TF content and degradability for both leaf and leaf + leaf-stalk. Thus, BS leaf and leaf + leaf-stalk samples from 15 to 30 days of age were used for flavonoid extraction and used in the Experiment 2. Experiment 2 was conducted according to a 3 × 5 factorial experiment. Three roughage to concentrate (R:C) ratios at 50:50, 40:60, and 30:70 were used, and five levels of flavonoid extract (FE) at 0, 10, 20, 30, and 40 mg of substrate dry matter (DM) were supplemented. Experiment 2 showed that R:C ratio and FE had an interaction effect only on acetate to propionate ratio. Varying R:C ratios significantly increased (p < 0.05) in vitro DM degradability, total volatile fatty acids (VFA), and propionate (C3) concentration. FE supplementation linearly (p < 0.05) increased total VFA and C3 concentration and decreased methane production and protozoal population. This study could conclude that FE from BS could effectively modulate ruminal fermentation and decrease methane production. However, in vivo study needs to elucidate in order to validate the present results.
Keywords: Brazilian spinach; Flavonoids; Maturity; Methane mitigation; Protozoa